2007
DOI: 10.2353/ajpath.2007.060647
|View full text |Cite
|
Sign up to set email alerts
|

Annexin 2 Regulates Intestinal Epithelial Cell Spreading and Wound Closure through Rho-Related Signaling

Abstract: Epithelial cell migration is a critical event in gastrointestinal mucosal wound healing and is dependent on actin cytoskeletal reorganization. We observed increased expression of an actin regulatory protein, annexin 2, in migrating intestinal epithelial cells. Small interfering RNA (siRNA)-mediated knockdown of annexin 2 expression in Caco-2 epithelial cells resulted in significant reductions in cell spreading and wound closure associated with decreased formation of filamentous actin bundles along the base of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 56 publications
4
83
1
Order By: Relevance
“…Whether S100A6 contributes to pancreatic cancer cell motility through interaction with annexin 2 is not yet clear. However, the observed positive correlation in this study between high S100A6 levels and the localisation of annexin 2 to the plasma membrane in pancreatic cancer cells may have significance with respect to the ability of these cells to move, as annexin 2 has been implicated in the regulation of actin dynamics, cell spreading and wound closure (Hayes et al, 2006;Babbin et al, 2007;de Graauw et al, 2008). Hayes et al showed that annexin 2 was concentrated in the dynamic actin-rich protrusions of motile cells and that siRNA-mediated depletion of annexin 2 led to loss of protrusive and retractile activity (Hayes et al, 2006).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Whether S100A6 contributes to pancreatic cancer cell motility through interaction with annexin 2 is not yet clear. However, the observed positive correlation in this study between high S100A6 levels and the localisation of annexin 2 to the plasma membrane in pancreatic cancer cells may have significance with respect to the ability of these cells to move, as annexin 2 has been implicated in the regulation of actin dynamics, cell spreading and wound closure (Hayes et al, 2006;Babbin et al, 2007;de Graauw et al, 2008). Hayes et al showed that annexin 2 was concentrated in the dynamic actin-rich protrusions of motile cells and that siRNA-mediated depletion of annexin 2 led to loss of protrusive and retractile activity (Hayes et al, 2006).…”
Section: Discussionmentioning
confidence: 69%
“…Hayes et al showed that annexin 2 was concentrated in the dynamic actin-rich protrusions of motile cells and that siRNA-mediated depletion of annexin 2 led to loss of protrusive and retractile activity (Hayes et al, 2006). More recently, Babbin et al (2007) observed that depletion of annexin 2 from Caco-2 epithelial cells resulted in reductions in cell spreading and wound closure. Finally, the work of de Graauw et al (2008) pointed towards the phosphorylation of annexin 2 as a key event in the remodelling of the actin cytoskeleton during cell spreading.…”
Section: Discussionmentioning
confidence: 96%
“…39). RNAimediated silencing of AnxA2 impairs the migration of human epithelial colorectal adenocarcinoma cells (40) and glioma cells (41) and reduces the invasiveness of breast cancer cells (18), all highlighting the potential importance of AnxA2 in cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Closure-We have previously reported that AnxA2 is up-regulated in migrating IECs and controls cell motility and wound closure (13). To further identify the mechanisms by which AnxA2 regulates epithelial cell motility, we generated cell lines with stable down-regulation of AnxA2 using two different shRNA sequences (shAnxA2) and a control cell line with a nonsilencing shRNA target (shCtrl).…”
Section: Anxa2 Promotes Epithelial Cell Migration and Woundmentioning
confidence: 99%
“…We have previously reported that the calcium-dependent phospholipid binding protein, annexin A2 (AnxA2), facilitates IEC migration (13). AnxA2 is a highly conserved protein in invertebrates and plants and is expressed in most cell types.…”
mentioning
confidence: 99%